2010
DOI: 10.1186/1471-2180-10-115
|View full text |Cite
|
Sign up to set email alerts
|

Production of enterodiol from defatted flaxseeds through biotransformation by human intestinal bacteria

Abstract: BackgroundThe effects of enterolignans, e.g., enterodiol (END) and particularly its oxidation product, enterolactone (ENL), on prevention of hormone-dependent diseases, such as osteoporosis, cardiovascular diseases, hyperlipemia, breast cancer, colon cancer, prostate cancer and menopausal syndrome, have attracted much attention. To date, the main way to obtain END and ENL is chemical synthesis, which is expensive and inevitably leads to environmental pollution. To explore a more economic and eco-friendly produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…Although Wang et al (2010) obtained a group of mixed bacteria able to metabolise flaxseed to produce END with potential application for large-scale production of enterolignans, END and ENL have not been produced commercially as a supplement so far.…”
Section: Health and Lignansmentioning
confidence: 96%
See 2 more Smart Citations
“…Although Wang et al (2010) obtained a group of mixed bacteria able to metabolise flaxseed to produce END with potential application for large-scale production of enterolignans, END and ENL have not been produced commercially as a supplement so far.…”
Section: Health and Lignansmentioning
confidence: 96%
“…Accordingly, Wang et al (2010) obtained a bacterial consortium, designated as END-49, which transformed flaxseed to END. Based on analysis using pulsed field gel electrophoresis, END-49 was found to consist of five genomically distinct bacterial lineages.…”
Section: Microbiota Responsible For the Conversion Of Plant Lignans Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher intakes (up to 13.5 mg/day) have been found in Germany [12]. Lignans are expected to have beneficial effects in humans after fermentative conversion in the colon to the mammalian lignans ENL and END [13,14]. Subpopulations with higher consumption of lignans display considerable lower disease frequency [7,[15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Gut microbiota can metabolize certain plant-derived foods into biologically active compounds, e.g., enterolignans, that may play a role in carcinogenesis. 148 A recent meta-analysis indicated that these phytohormones may decrease the incidence of breast cancer. 149 The highest production of carcinogens was associated with gut anaerobic bacteria and was lowered by supplementation with live lactobacilli.…”
Section: Cancermentioning
confidence: 99%